2016
DOI: 10.1007/s12519-016-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity induced by acute and chronic paracetamol overdose in children: Where do we stand?

Abstract: Chronic paracetamol poisoning is a potential risk factor for hepatotoxicity and acute liver failure. Delays in seeking medical help might be a contributing factor. Clinicians should have a higher index of clinical suspicion for this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
2
9
0
14
Order By: Relevance
“…It was evidenced that patients with chronic intake were more likely to develop hepatic encephalopathy at any time of clinical evolution than patients with acute ingestion. Similar results were obtained in the study conducted at our hospital, where retrospectively evaluated cases with suspected paracetamol intake in both adults and children, it was observed that patients with chronic paracetamol intake were at higher risk of developing ALF than patients with acute ingestion (8,13) .…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It was evidenced that patients with chronic intake were more likely to develop hepatic encephalopathy at any time of clinical evolution than patients with acute ingestion. Similar results were obtained in the study conducted at our hospital, where retrospectively evaluated cases with suspected paracetamol intake in both adults and children, it was observed that patients with chronic paracetamol intake were at higher risk of developing ALF than patients with acute ingestion (8,13) .…”
Section: Introductionsupporting
confidence: 87%
“…In an epidemiological study, the relative risk (RR) of acute liver failure with therapeutic doses of paracetamol was 7 (CI 99%: 3.3 -13.9) with an estimated incidence rate of 2.4 cases per 100,000 person-years of exposure (11) . In our retrospective study, we found that only 1 of 49 patients with acute poisoning showed hepatotoxicity, whereas 7 of 8 patients with chronic poisoning showed hepatotoxicity, of which 3 met criteria of acute liver failure (8) .…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In children, on the contrary, random poisoning prevails [54,56]. For the elderly, suicidal attempts are not characteristic: self-medication, accidental poisoning or the erroneous use of multicomponent drugs, which include paracetamol, predominate [27,39].…”
Section: возрастmentioning
confidence: 99%
“…2), то доля преднамеренных самоотравлений с участием препарата значительно выше -от 47,8 до 90%, а в отдельных регионах, социальных или возрастных группах может приближаться практически к 100%. Table 2 Доля преднамеренных самоотравлений при передозировке парацетамола, % / The proportion of intentional self-poisoning in case of an overdose of Paracetamol, % Страна / Сountry % Австралия / Australia [23,26] 85-90 Швеция / Sweden [36] 85 Швейцария / Switzerland [37] 79 Сингапур / Singapore [24] 76,8 Польша / Poland [38] 68,2 Испания / Spain [39] 47,8 Россия / Russia [21] 60* Беларусь / Belarus [40] 78,6* *Для всех отравлений медикаментами / *for all drug poisonings Например, в Австралии лишь 0,02% подростков сообщали о случайном супратерапевтическом приёме парацетамола [25].…”
unclassified